2015
DOI: 10.1103/physrevlett.115.228304
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and Contact Contributions to Continuous Shear Thickening in Colloidal Suspensions

Abstract: Shear thickening is a widespread phenomenon in suspension flow that, despite sustained study, is still the subject of much debate. The longstanding view that shear thickening is due to hydrodynamic clusters has been challenged by recent theory and simulations suggesting that contact forces dominate, not only in discontinuous, but also in continuous shear thickening. Here, we settle this dispute using shear reversal experiments on micron-sized silica and latex particles to measure directly the hydrodynamic and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
218
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(235 citation statements)
references
References 40 publications
14
218
0
3
Order By: Relevance
“…The suspension was indeed found to follow two separate viscosity curves with distinct critical volume fractions, depending on what shear rate was applied. A similar suspension was investigated under shear reversal (15), during which the viscosity first drops to a low value set by hydrodynamic interactions before increasing to a plateau dominated by contact interactions (16). As expected in such a framework, only the contact contribution to the viscosity increases with increasing shear rate, confirming the key role of contacts in shear-thickening suspensions.…”
mentioning
confidence: 52%
“…The suspension was indeed found to follow two separate viscosity curves with distinct critical volume fractions, depending on what shear rate was applied. A similar suspension was investigated under shear reversal (15), during which the viscosity first drops to a low value set by hydrodynamic interactions before increasing to a plateau dominated by contact interactions (16). As expected in such a framework, only the contact contribution to the viscosity increases with increasing shear rate, confirming the key role of contacts in shear-thickening suspensions.…”
mentioning
confidence: 52%
“…Motivated by this picture, we introduce a simple model which combines these frictional and hydrodynamic contributions and accurately fits the measured viscosity over a wide range of particle volume fraction and shear stress. There is mounting evidence from recent experiments [1,2] and simulations [3] suggesting that contact friction plays a dominant role in colloidal shear thickening, however this assertion is controversial because of contrary evidence. While friction-based models and simulations capture the viscosity increase observed in experiments, other experimental signatures, particularly the stress anisotropy, are at odds with expectations for frictional interactions [4].…”
mentioning
confidence: 99%
“…Only a handful of experiments measure N 1 in shear thickening colloids, though most report N 1 < 0 [4,[28][29][30], consistent with lubrication forces; the lone exception is a study using roughened particles [31]. Recent experimental evidence for friction-driven colloidal shear thickening focuses on the viscosity alone, either comparing viscosity profiles to friction-based models [1] or using shear-reversal techniques to separate contributions from hydrodynamic and contact forces [2], and thus these experiments do not address this discrepancy in the sign of N 1 .In this Letter we address this disagreement between friction-based models and experiments. Detailing the behavior of both the viscosity η(σ, φ) and N 1 (σ, φ) over a wide range of shear stresses and volume fractions in colloidal silica spheres exhibiting continuous shear thickening, we show that negative contributions to N 1 from lubrication forces can mask positive frictional contributions at moderate volume fractions, but at sufficiently high volume fractions and stresses, frictional interactions become dominant and N 1 transitions from negative to positive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that mildly dense suspensions are dense enough for contact forces to develop during thickening [48]. Lin et al [49] conducted shear reversal experiments to observe the relative contribution of hydrodynamic and contact forces in micro-size suspensions. The contact forces were said to be zero at the reversal stage of the experiments, while assuming that the microstructure remained unchanged and the hydrodynamic forces were identical in magnitude but reversed in direction.…”
Section: Discussionmentioning
confidence: 99%